Evaluating the performance of insurance companies using the balanced scorecard. An Empirical study - Samay, Ali; Ouledbrahim, Laila (Dirassat Journal Economic Issue, 2016)
This study aims to evaluate the performance of insurance companies using the balanced scorecard, to achieve the objectives of the study, we designed a questionnaire in order to test hypotheses and answer the study questions. we distributed (55 questionnaires) on sample of the study and (49quastionnaires) has been retrieved, and it has been analysed by SPSS. And we have used also inductive and descriptive methodology. the study found that insurance companies use the scorecard with its four dimensions, as well as one of the most important results is the lack of differences statistically significant at α≤ 0.05among interviewees responses averages about using scorecard as a tool to assess the performance of insurance companies due to personal factors. The study also found a set of recommendations as preparing intensif training courses for the staff on how to implement modern management methods, the study also recommended to encourage insurance companies to apply the balanced scorecard as a tool to assess overall performance.